Field trip - Brooks, Molly (Molly Grayson) (Los Angeles ; New York : Disney Hyperion, 2019)
When Sanity and Tallulah are separated from their classmates during a disastrous field trip to a mining planet, they must rely on their creativity and problem-solving skills to save the day.
"A Junior Library Guild Selection"--Inside front flap dust jacket.
Keywords: Graphic novels; School field trips -- Fiction; Planets -- Fiction; Science fiction; Graphic novels